Preliminary Experience with a Novel System of Facet Fixation to Treat Patients with Lumbar Degenerative Disease. A New Perspective in Minimally Invasive Spine Surgery? - Francaviglia, Natale; Costantino, Gabriele; Villa, Alessandro; Iacopino, Domenico Gerardo; Pappalardo, Maria Pia; Barone, Fabio; Gallo, Cristina; Contino, Antonino Odierna; Meli, Francesco; Maugeri, Rosario (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Purpose We report our experience with a novel surgical device for the treatment of lumbar degenerative microinstability. Facet Wedge (DePuy Synthes, Raynham, Massachusetts, United States) is a novel technique of intra-articular lumbar facet fixation that provides a minimally invasive alternative to standard posterior fixation.Materials and Methods From November 2014 to July 2015, 38 patients underwent single-level Facet Wedge implantation. The main surgical indications included herniated disk (18 patients), spinal canal and foraminal stenosis (14 patients), and Meyerding grade I degenerative spondylolisthesis (6 patients). All the patients showed radiologic signs of microinstability: hyperintensity in both facet joints (facet fluid signal) in T2-weighted magnetic resonance imaging and a black disk as a sign of degenerative disease. No slippage was evident at dynamic radiograph. After a period of conservative treatment (minimum of 6 months), surgery was performed. All patients' follow-up lasted over at least 12 months.Results The low back visual analog scale score decreased significantly after surgery (from an average of 8.2 to 3.1 at final follow-up). Postoperatively, the Oswestry Disability Index showed a significant reduction (14.7 on average). No slippage or signs of adjacent segment degeneration was detected in neuroimaging follow-up.Conclusion Facet Wedge allows facet fixation in lumbar degenerative microinstability. To the best of our knowledge, this is the first clinical series reported in the literature on this novel device.
Keywords: degenerative lumbar disease; facet fluid signal; facet wedge; facet fusion; microinstability